Comparison of Organizational Climate in the Regional Unit of the National Institute of Public Health Before and After Reorganization - Gašper Jordan; Gozdana Miglič; Miha Marič (Central European Public Administration Review)
Organizations have been focused on organizational climate (OC) as one of the influencing factors, which has an impact on organizational outcomes, attaining organizational goals and employee satisfaction. Our research focuses on the regional unit of the National Institute of Public Health in Slovenia and the comparison of the OC before (2013) and after reorganization (2015). We used a modified SiOK (Slovenian Organizational climate) questionnaire to shed light on employees’ perception of OC. OC and reorganization are closely connected on account of the relationship between management and employees; if OC is positive, we can expect less complicated process of reorganization as it can be if it is negative. The research revealed misfired attempt of OC improvement in all dimensions, though we expected ameliorated results in the three worst assessed OC dimensions before reorganization. Further, in the paper several recommendations are suggested to managers facing reorganization.